Grabfood Application Marketing Strategy in Increasing Online Sales of Ramen Master Kediri - Putri, Nabila Alfina; Hakimah, Ema Nurzainul (Proceeding Kilisuci International Conference on Economic & Business, 2025)
Research aim : Analyzing the effectiveness of digital marketing strategies through the GrabFood application in increasing sales of Ramen Master in Kediri, on factors such as discounts, ease of use of the application, product quality, and service.  Design/Methode/Approach : Qualitative research method with a phenomenological approach, using in-depth interviews with 4 informants. And data analysis uses a triangulation process to ensure the validity of the research results..  Research Finding : The results show that Ramen Master's innovative marketing strategy through GrabFood has yielded impressive results by significantly increasing sales. The combination of competitive pricing, ease of use of the app, consistent product quality, and timely service has made Ramen Master the top choice for ramen lovers.  Theoretical contribution/Originality : This research can provide new insights into the role of food delivery platforms in increasing culinary sales, especially in terms of choosing the right marketing strategy.  Practitionel/Policy implication : The research results can be used as a reference for the development of other culinary marketing strategies and the improvement of grabfood services.  Research limitation : This research only focuses on culinary trends in specific regions and may not reflect national or global trends. In addition, the influence of social media on the formation and spread of trends also needs further research.